Does Diplomacy Promote International Trade? The Case of Ukraine - Leonid Raneta; Mykhaylo Kunychka (Czech Journal of International Relations, 2015)
The purpose of this paper is to analyze the impact of the commercial diplomacy of Ukraine on its export. Within this field of research we mutually compare various official representations abroad and their effects on export flows. We consider embassies, consulates general and honorary consulates as commercial diplomacy actors abroad. The main contribution of the paper is that it is the first empirical study of Ukrainian commercial diplomacy in terms of export promotion. We use an empirical trade model to verify the impact of economic, cultural, geographical and diplomatic factors on Ukrainian exports. The panel data incorporates 1386 export flows to 198 destinations during the period from 2007 to 2013. In the end, we conclude that embassies are more relevant instruments of export stimulation than consulates general or honorary consulates.